Removal of toxic metals from vanadium-contaminated soils using a washing method: Reagent selection and parameter optimization. (August 2017) - Jiang, Jianguo; Yang, Meng; Gao, Yuchen; Wang, Jiaming; Li, Dean; Li, Tianran
Abstract: Vanadium (V) contamination in soils is an increasing worldwide concern facing human health and environmental conservation. The fractionation of a metal influences its mobility and biological toxicity. We analyzed the fractionations of V and several other metals using the BCR three-step sequential extraction procedure. Among methods for removing metal contamination, soil washing is an effective permanent treatment. We conducted experiments to select the proper reagents and to optimize extraction conditions. Citric acid, tartaric acid, oxalic acid, and Na2 EDTA all exhibited high removal rates of the extractable state of V. With a liquid-to-solid ratio of 10, washing with 0.4 mol/L citric acid, 0.4 mol/L tartaric acid, 0.4 mol/L oxalic acid, and 0.12 mol/L Na2 EDTA led to removal rates of 91%, 88%, 88%, and 61%, respectively. The effect of multiple washing on removal rate was also explored. According to the changes observed in metal fractionations, differences in removal rates among reagents is likely associated with their pKa value, pH in solution, and chemical structure. We concluded that treating with appropriate washing reagents under optimal conditions can greatly enhance the remediation of vanadium-contaminated soils. Highlights: Soil washing technology was applied to treat V-contaminated soil. The V-forms were analyzed using the BCR three-step sequential extraction procedure. Citric acid, tartaric acid, oxalic acid, and Na2 EDTA exhibited V-high removal rate. Concentration of reagents, liquid-to-solid ratio, and washing times were optimized. V removal mechanism of different washing reagents was discussed.